2012
DOI: 10.1177/239700221202600208
|View full text |Cite
|
Sign up to set email alerts
|

On the Motives and Needs for Work beyond Age 65: Comparing Voluntary Workers versus Agency Workers

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Many types of work activities take place in a social environment and therefore align with self‐transcendence work values. These findings are consistent with those of previous studies using related constructs (e.g., Torka et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Many types of work activities take place in a social environment and therefore align with self‐transcendence work values. These findings are consistent with those of previous studies using related constructs (e.g., Torka et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Relationships with others and altruism can be found in voluntary and paid work because workplaces usually allow for social gathering through contact with supervisors, colleagues, clients, or external organizations. Recently, Torka, Goedegebure, Van Ewijk, and Looise () found that social motives were equally important for post‐retirement volunteers and post‐retirement agency workers. Thus, the type of work activity may be of secondary importance in meeting self‐transcendence work values.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous research has shown that generativity can be a motive for continuing to work past normal retirement age (Dendinger et al., 2005; Templer et al., 2010; Torka et al., 2012). Perhaps job quality is part of a more complicated longer term process; workers enjoy and are likely reluctant to leave the intrinsically rewarding work that, over time, led to their heightened perception of generativity.…”
Section: Resultsmentioning
confidence: 99%
“…It however has the advantage of including reliable and largescale information on work behavior of older employees from many birth cohorts. Studies on the relationship between financial incentives and work beyond retirement so far typically relied on small-scale and potentially specific populations (Kim and Feldmann 2000;Saba and Guerin 2005;Torka et al 2012) or on survey-based data that may be affected by self-selection and measurement error in key variables (Anger et al 2018;Büsch et al 2010;Dittrich et al 2011;Kanabar 2015;Pfarr andMaier 2015, Saba andGuerin 2005).…”
Section: Estimation Samplementioning
confidence: 99%